CpG Oligodeoxynucleotide Promotes Apoptosis of Human Bladder Cancer T24 Cells Via Inhibition of the Antiapoptotic Factors. (23rd September 2019) - Luo, Yang; Dong, Yuhang; Liang, Shengran; Yuan, Lihong; Men, Hongsheng; Zhang, Shulin; Tian, Sujuan; Fu, Xiaoyi; Dong, Bin; Meng, Minjie
Objective: Unmethylated cytosine-phosphorothioate-guanine oligodeoxynucleotide, a synthetic oligodeoxynucleotide, has been used as an adjuvant in clinic and in the antitumor activity. However, the antitumor mechanism of cytosine-phosphorothioate-guanine oligodeoxynucleotide against human bladder cancer is unknown. The purpose of this study is to evaluate the cytotoxicity and molecular mechanism of anticancer effect of cytosine-phosphorothioate-guanine oligodeoxynucleotide on T24 cells (a human bladder cancer cell line). Methods: The cytotoxic activity of cytosine-phosphorothioate-guanine oligodeoxynucleotide was examined by cell viability assay in the presence and absence of 5-fluorouracil, respectively. Apoptosis and cell-cycle phase distribution were detected by flow cytometry analysis. To investigate the molecular mechanisms of cytosine-phosphorothioate-guanine oligodeoxynucleotide cytotoxicity, the expression of antiapoptotic factors (B-cell lymphoma-2 and Survivin, β-actin as control) in RNA, and protein level was assayed by quantitative real-time polymerase chain reaction and automated capillary Western blot. Results: The inhibition ratio of T24 cells treated with both cytosine-phosphorothioate-guanine oligodeoxynucleotide and 5-fluorouracil was higher than those treated with either cytosine-phosphorothioate-guanine oligodeoxynucleotide or 5-fluorouracil alone. In the combination group (cytosine-phosphorothioate-guanine oligodeoxynucleotide and 5-fluorouracil), the apoptosis rate was significantly increased, and more cells were arrested at "S" and "G2/M" phases compared to those in cytosine-phosphorothioate-guanine oligodeoxynucleotide or 5-fluorouracil alone. Furthermore, the expression of antiapoptotic factors was decreased by cytosine-phosphorothioate-guanine oligodeoxynucleotide alone or combined with 5-fluorouracil. Conclusion: Cytosine-phosphorothioate-guanine oligodeoxynucleotide promoted apoptosis and enhanced the chemosensitivity of 5-fluorouracil in T24 cells. Cytosine-phosphorothioate-guanine oligodeoxynucleotide downregulated the expression of antiapoptotic factors and inhibited cell-cycle phase by arresting more cells at "S" and "G2/M" phases. This study indicated the potential ability of cytosine-phosphorothioate-guanine oligodeoxynucleotide as a candidate drug for human bladder cancer.